Ultrasound-assisted optimized extraction and analysis of polysaccharides of Tricholoma matsutake - Xu, Cheng-Jian; Yi, Yu-Wen; Liu, Yang; Zhou, Yu; Lin, Dan; Zhu, Zhong-Yan; Zhu, Nan; Xiao, Hang (Frontiers in Sustainable Food Systems, 2024)
The ultrasound-assisted extraction technique was used for extracting polysaccharides of Tricholoma matsutake (PTM) in this work. The effects of different parameters, i.e., solid-to-liquid ratio, ultrasonic power, extraction time, and extraction temperature on the PTM yield were optimized using a rotatable, orthogonal central composite design. In the derived optimal conditions, the PTM yield was 16.97 ± 0.06%, which corresponded well with the regression model predicted value of 16.85%. The extracted PTM was purified, and the structural characteristics and antioxidant activities were investigated. The PTM was found to be composed mainly of fructose, mannose, glucose, and galactose with a molar molecular ratio of 1:2.25:9.35:5, and an average molecular weight of 90,100 Da. High antioxidant effects of PTM were seen in the tests of DPPH, hydroxyl, and ABTS radical scavenging, along with a moderate superoxide radical scavenging rate.